Kajian Literatur Tanaman Sirih Merah, Binahong, Dan Pegagan Sebagai Penyembuh Luka Insisi: Literature Study of Red Betel Plants, Binahong, and Gotu Kola as Incision Wound Healing - Salinding Irene Septiani; Dewi Mayasari; Fajar Prasetya (Proceeding of Mulawarman Pharmaceuticals Conferences, 2021)
Injury is a condition where tissue function and structure of the body are damaged. Incision wounds can occur intentionally or unintentionally by sharp or blunt instrument. Red betel plants, binahong, and gotu kola are plants that can heal an incisioun wound. The results are obtained by the method of collecting data which related to the study that being studied and analyzed descriptively. The results obtained indicate the secondary metabolites that play a role in incision wound healing process are flavonoids, tannins, and triterpenoids.